The spacewise dependent source identification problem for the elliptic-telegraph differential equation with involution and Robin condition - Allaberen Ashyralyev; Ahmad Al-Hammouri (E-Journal of Analysis and Applied Mathematics)
In the present paper, the spacewise dependent source identification problem (SIP) for the elliptic-telegraph differential equation with involution and Robin condition is investigated. The theorem on stability estimates for the solution of this space-wise dependent SIP is established.